Nephrine-Albumin Interaction and the Spontaneous Apparition of Series Capacitors in the Renal Glomerulus as Indicator of Kidney Disease - Nieto-Chaupis, Huber (2022)
The abundance of dipoles of glucose in the blood stream would give rise to a pushing out of albumin proteins giving origin to the formation of a biolelectric circuit inside renal glomerulus. In the periods of large amounts of glucose and albumin in blood, kidneys might not be able to filter proteins initializing the interaction protein-protein at the renal glomerulus. From this nephrine and albumin interaction can be seen as a capacitor because the anionic and cationic functions of proteins. This paper have paid attention to the physics of renal glomerulus when it is electrically involved due to the presence of albumin that surpasses the different layers of renal glomeulus becoming a strong indicator of the kidney disease.